Bioassay‐Based Isolation and Identification of Phenolics from Sweet Cherry That Promote Active Glucose Consumption by HepG2 Cells. Issue 2 (5th January 2015) - Cao, Jinping; Li, Xin; Liu, Yunxi; Leng, Feng; Li, Xian; Sun, Chongde; Chen, Kunsong
Abstract A variety of phenolics had been found to be functional in promoting cellular glucose consumption that is important for blood glucose regulation. Sweet cherry (Prunus avium) is rich in such kinds of phenolics, including hydrocinnamic acids, anthocyanins, flavonols, and flavan‐3‐ols. Furthermore, a sweet cherry phenolics‐rich extract (PRE) was found to be effective in promoting HepG2 glucose consumption. Seventeen components were preliminarily identified by HPLC‐ESI‐MS, including 9 hydrocinnamic acids, 4 anthocyanins, 3 flavonols, and 1 flavan‐3‐ol. To investigate the cellular glucose consumption‐promotion activity of different phneolics subclasses, the phenolics were further fractionated into an anthocyanin‐rich fraction (ARF), hydrocinnamic acid‐rich fraction (HRF), and flavonol‐rich fraction (FRF) through liquid–liquid extraction and mix‐mode cation‐exchange solid‐phase extraction. The 3 fractions promoted HepG2 glucose consumption to different levels, with the promotion effects of HRF and FRF stronger than that of the ARF. The results provide guidance on the use of sweet cherry as a functional fruit.